2020
DOI: 10.1001/jamasurg.2020.2828
|View full text |Cite
|
Sign up to set email alerts
|

Intersectionality of Gender and Visible Minority Status Among General Surgery Residents in Canada

Abstract: IMPORTANCE Within medical specialties, surgical disciplines disproportionately and routinely demonstrate the greatest underrepresentation of women and individuals from racial/ethnic minority groups. Understanding the role that diversity plays in surgical resident training may identify strategies that foster resident resiliency, optimize surgical training, and improve patient outcomes. OBJECTIVE To examine the implication of gender and visible minority (VM [ie, nonaboriginal people who are not White individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
1
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 37 publications
1
53
1
3
Order By: Relevance
“…Le profession nalisme dont les apprenants font l'expérience dans les pro grammes de formation n'est cependant pas neutre sur plan de la race. Au Canada, les médecins résidents racisés des pro grammes de chirurgie indiquent que leurs compétences sont remises en question plus souvent que celles de leurs pairs de même genre, et ils ont moins confiance de voir appliquer des mesures adéquates s'ils signalent de la discrimination (ce qui, en soi, est souvent considéré comme un geste non profession nel) 8 . Les conclusions d'une récente étude qualitative menée auprès d'étudiants américains appartenant à des groupes sous représentés dans la profession médicale montrent également que les étudiants racisés doivent travailler activement à déman teler les stéréotypes nuisibles pour réussir à faire correspondre leurs identités professionnelle (comme médecin) et raciale 9 .…”
Section: Jamc | 22 Mars 2021 | Volume 193 | Numéro 12 E437unclassified
“…Le profession nalisme dont les apprenants font l'expérience dans les pro grammes de formation n'est cependant pas neutre sur plan de la race. Au Canada, les médecins résidents racisés des pro grammes de chirurgie indiquent que leurs compétences sont remises en question plus souvent que celles de leurs pairs de même genre, et ils ont moins confiance de voir appliquer des mesures adéquates s'ils signalent de la discrimination (ce qui, en soi, est souvent considéré comme un geste non profession nel) 8 . Les conclusions d'une récente étude qualitative menée auprès d'étudiants américains appartenant à des groupes sous représentés dans la profession médicale montrent également que les étudiants racisés doivent travailler activement à déman teler les stéréotypes nuisibles pour réussir à faire correspondre leurs identités professionnelle (comme médecin) et raciale 9 .…”
Section: Jamc | 22 Mars 2021 | Volume 193 | Numéro 12 E437unclassified
“…Although women make up an estimated 70% of the global healthcare workforce, they are underrepresented in multiple distinct elds [11,12]. The gender variable has been associated with adverse implications while choosing the surgical eld, training for residency programs, and daily working in medical practice [13][14][15]. When appraising the intersections with minorities based on race, sexuality, and socioeconomic class, the gap expands [14,16,17].…”
Section: Policy Implicationsmentioning
confidence: 99%
“…This feature was pervasive in sessions related to NSOAPs, intersectionality, and social justice. For example, existing supportive bene ts, like parental leave, and mechanisms to report discrimination play a vital role in retaining these groups in the SOA elds [15]. Along with these strategies, promoting diversity and putting women and non-binary people in leadership helps to mitigate the pipeline effect [16,18].…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Racialized residents in Canadian surgical programs have reported that their competence was questioned more often than that of their gender-matched peers, and they felt less confident that their reports of discrimination (often itself considered to be an unprofessional act) would lead to appropriate action being taken. 8 Indeed, the findings of a recent qualitative study of US physician-trainees considered underrepresented in medicine suggest that racialized students must actively work to dismantle harmful stereotypes to be able to align their professional (physician) and racial identities. 9 …”
mentioning
confidence: 99%
“…Racialized residents in Canadian surgical programs have reported that their competence was questioned more often than that of their gender-matched peers, and they felt less confident that their reports of discrimination (often itself considered to be an unprofessional act) would lead to appropriate action being taken. 8 Indeed, the findings of a recent qualitative study of…”
mentioning
confidence: 99%